PERSEPSI PELAJAR DALAM KEMAHIRAN PSIKOMOTOR PEMASANGAN KIT MODEL KERETA MENGGUNAKAN CD INTERKATIF - Ali, Azita; Zakaria, Normah; Khamis, Lizawati (Online Journal for TVET Practitioners, 2018)
The Learning of living skills in schools becoming more challenging nowadays. It triggers competition as the world approaching globalism in this 21st century. The modernisation of technology helps in overcoming the gap of difficulties and challenging that humans have to face. This study was conducted in order to determine the students' perception psychomotor skills installation kit car model with the usage of interactive CD. The sample of this study consists of 92 respondent of gender dissimilarity from different schools around Mersing. The questionare of 32 items is used as an instrument in this study. The pilot study was conducted at Sekolah Rendah Agama Bersepadu Mersing with the number of 30 respondents. The mean value of the result based on the item of interest is 4.60 and mean value of the attitude is 4.67 using Statistical Package for the Social Sciences (Version 22.0) the perform data analysis. The analysis of data includes the mean score percentage and correlation. This study found the usage of an interactive CD in psychomotor skills model car kit installation is on the higher level. This result shows that the utilization of interactive CD is highly recommended to be implemented in schools since it is attractive useful and helpful in shaping the behaviour and attitude of the students in achieving a topic.